Executive board composition and bank risk taking - Berger, Allen N.; Kick, Thomas; Schaeck, Klaus (Journal of Corporate Finance, 2014)
Little is known about how the demographic characteristics of executive teams affect corporate governance in banking. Exploiting a unique dataset, we investigate how age, gender, and educational composition of executive teams affect the portfolio risk of financial institutions. Using difference-in-difference estimations that focus exclusively on mandatory executive retirements for the entire population of German bank executive officers, we demonstrate that younger executive teams increase portfolio risk, as do board changes that result in a higher proportion of female executives, although this latter effect is weaker in terms of both statistical and economic significance. In contrast, when board changes increase the representation of executives holding Ph.D. degrees, portfolio risk declines.